Giant isotropic magneto-thermal conductivity of metallic spin liquid candidate Pr2Ir2O7 with quantum criticality - J. M. Ni (Nature Portfolio, 2021)
Pr2Ir2O7 is a candidate for a metallic spin liquid with a quantum critical point; however, the exact nature of its ground state and quantum criticality is unknown. Here, the authors report strong deviations from dipolar spin-ice ground state and find normal electronic behavior near quantum criticality.